Paired-Pulse Depression of Unitary Quantal Amplitude at Single Hippocampal Synapses - Chen, Gong; Harata, Nobutoshi C.; Tsien, Richard W. (Proceedings of the National Academy of Sciences - PNAS, 2004)
At central synapses, quantal size is generally regarded as fluctuating around a fixed mean with little change during short-term synaptic plasticity. We evoked quantal release by brief electric stimulation at single synapses visualized with FM 1-43 dye in hippocampal cultures. The majority of quantal events evoked at single synapses were monovesicular, based on examination of amplitude distribution of a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-receptor-mediated responses. Consistent with previous findings, the quantal size did not change during paired-pulse facilitation (PPF), supporting the notion that the evoked events were monoquantal. However, during paired-pulse depression (PPD), there was a significant decrease in unitary quantal size, which was not due to postsynaptic receptor desensitization. This asymmetry of quantal modulation during PPF and PPD was demonstrated at the same single synapse at different extracellular calcium concentrations. Our results indicate that PPF can be fully accounted for by an increase of release probability, whereas PPD may be caused by decreases in both release probability and quantal size. One possible explanation is that the release of a quantum of neurotransmitter from synaptic vesicles is not invariant but subject to rapid calcium-dependent modulation during short-term synaptic plasticity.